Genomic comparison of esophageal squamous cell carcinoma and its precursor lesions by multi-region whole-exome sequencing - Xi-Xi Chen (Nature Portfolio, 2017)
The pathogenesis of oesophageal squamous cell carcinoma is a multi-step process but the genetic determinants behind this progression are unknown. Here the authors use multi-region exome sequencing to comprehensively investigate the genetic evolution of precursor dysplastic lesions and untransformed oesophagus.